O papel do fetichismo na produção da consciência humana: materialidade e idealidade em Karl Marx - Cavalcante, Vítor Valente (2016)
This study sought to reconstruct the elements left by Marx that assist in building a fetish theory reviewing the place of this concept in the thought of the author in question. The hypothesis that guides research is that there is no way to understand the theories of Marx without understanding its epicurean ontology, from the clues left in his professorial thesis, or, more broadly, in the period 1835-1841 . Thus, during the research it was necessary to establish an overview of the ontological foundations of Marx's thought and place of fetishism, in addition to the stroke path, analyzing the evolution of the concept of fetishism in the light of wider horizon of his thought, weaving a summary of the most relevant passages considered in the path taken by this influential advocate of socialism around the theme. Therefore, we established a dialogue with some theoretical fetish theory of the second half of the twentieth century and early twenty-first century, which, in most cases, or interpret Marx's thought as concrete itself and the laws of history which inevitably led to the victory of the proletariat, or identify their theory of value with the fetishism and reduce the ideology of the hegemony of exchange value and colonial prejudice of nineteenthcentury anthropology, advocating a purely rhetorical use of the concept in Marx. Finally, there are several key issues guided by today in order to establish some guidelines that helped to think the centrality of consciousness industry in the production of human life, insignia of the present day, when the production became immaterial and established a global system of fetishism in the struggle for consciousness, the arena in which it locks the clash between the main worldviews.